Perencanaan Ulang Struktur Gedung Dengan Kombinasi Shear Wall Dan Outrigger System Apartemen Grand Shamaya Surabaya Tower Aubrey - Muhammad Amri Imaduddin Maghribi; Ketut A Wiswamitra; Jojok Widodo S (Siklus : Jurnal Teknik Sipil, 2022)
Grand Shamaya Apartment Building, 44 Floor Apartment, is one of the buildings using a dual system construction. The system includes shear walls and moment-bearing frames (columns and beams) that work side by side to support lateral to gravity loads (earthquake and wind loads). The maximum load shear wall or 75% of the lateral load (wind and earthquake), and the size of the shear wall required is relatively large because it must withstand shear forces and bending moments. More treatment is needed to overcome this problem, namely by modifying the building's structure and adding an outrigger system. The Outrigger System itself is a wall component that functions as a one-floor beam. From the preliminary design, the column design is 1300mm x 1850 mm; beam measuring 900mm x 600 mm; plate thickness of 200 mm; shear wall thickness of 450 mm and outrigger design measuring 600 mm x 2000 mm thick. Then install the Outrigger System with axis positions T1 N ', T1 M', T1 E ', and T1 D' on floors 40 and 44. After re-analysis using the outrigger system, the deviation between floors can show a smaller value than before the outrigger system was applied. P-Delta effect control shows that the P-Delta effect in two structural directions can be neglected or safe because the maximum stability value of the structure in the X and Y directions is less than 0.09091. The latter fulfills the drift control. This result is the maximum value among several models that have been executed.